Sedulur Sikep Samin: antara Pandangan dan Sistem Pengetahuan - Hanifah Hikmawati (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This article discusses the knowledge system that exists in the community, along with Samin's Sikep, which has been reaping the pros and cons of the community. This assessment has become a stigma against Samin's existence from the past until now. This paper is a reflection of the anthropology carried out by researchers in the context of the knowledge system of the Sedulur Sikep Samin Blora community. The formulations of the problems in this journal are a) how Sedulur Sikep Samin builds awareness of the knowledge they have, b) how Sedulur Sikep interprets the principles of life in everyday life, c) how Sedulur Sikep builds the symbol of knowledge it has. The method used in this research is descriptive qualitative, with the results that describe the knowledge system assumptions of the Sedulur Sikep Samin Blora community to become the identity and symbol of the community itself as a knowledge-based society and a paradoxical, dynamic journey "to the truth", and multidimensional.